2020
DOI: 10.1002/rth2.12328
|View full text |Cite
|
Sign up to set email alerts
|

Is the time in therapeutic range on coumarins predicted by previous time in therapeutic range?

Abstract: Background The benefit of vitamin K antagonists depends on the time within the therapeutic range (TTR). A patient’s previous TTR could be a factor in the decision to change the anticoagulation regimen. However, the predictive value of a previous TTR for a future TTR is not well established, nor is it clear which TTR should prompt action. Objectives To investigate the predictive performance of a TTR and identify a threshold below which no recovery of TTR should be expected. Patients/Methods From 18 031 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…While this is a logical explanation, a study including more than 18,000 patients suggested that past INR stability does not predict future INR control. 14 Our data suggested no difference between the quality of warfarin management between types of ambulatory practice sites. This provides support that with standardized training, pharmacist-led warfarin management using point-of-care INR testing and decision-support software can be effective regardless of the setting.…”
Section: Original Researchmentioning
confidence: 53%
See 1 more Smart Citation
“…While this is a logical explanation, a study including more than 18,000 patients suggested that past INR stability does not predict future INR control. 14 Our data suggested no difference between the quality of warfarin management between types of ambulatory practice sites. This provides support that with standardized training, pharmacist-led warfarin management using point-of-care INR testing and decision-support software can be effective regardless of the setting.…”
Section: Original Researchmentioning
confidence: 53%
“…While this is a logical explanation, a study including more than 18,000 patients suggested that past INR stability does not predict future INR control. 14 …”
Section: Discussionmentioning
confidence: 99%
“…A Polish study, confined to younger patients with arbitrarily defined "unstable anticoagulation", found a marked increase in TTR after the switch [18]. Because both studies lacked a control group, and TTR is not stable over time [19], their results could be distorted by "regression" to the mean.…”
Section: Plos Onementioning
confidence: 99%